Journalistic coverage of migration in Ecuador during the 2020 states of exception - Márquez-Domínguez, Carmelo (2022)
We must wait for extraordinary catastrophes like the COVID-19 health crisis to appreciate a human rights approach in journalistic information. We set out to study the journalistic coverage of immigration in Ecuador during the state of exception decreed in 2020 with an analytical and comparative method with a mixed approach. On the one hand, we collected all the documentary production to understand the state of affairs; on the other hand, we analyzed the articles on migration and human mobility published in the digital editions of El Comercio and El Universo. The results show neutral referential frameworks, no human rights approaches or inclusive language, and a preference for news headlines and genres. Articles rarely include infographics, statistical data, or transmedia elements. Finally, the analysis showed a general depersonalization of authorship, a predominance of official sources, calls to order —in the face of chaos— and mainly Venezuelan immigrants being signaled as subjects.